Penerapan Metode Cooperative Integrated Reading and Composition (CIRC) dalam Pembelajaran Membaca Teks Arab di SMP Plus Al-Firdaus Malang - Dzat MR, Ahmad Faizal; Bashith, Abdul; Gafur, Abd (Shaut al Arabiyyah, 2023)
In learning to read Arabic texts, appropriate and fun learning methods are needed in order to realize interesting and effective learning. One method that can be used in learning to read Arabic text is Cooperative Integrated Reading and Composition (CIRC). This method can help students to improve their Arabic text reading skills. This study aims to describe the application of the CIRC method and its effectiveness in learning to read Arabic text. This research is an experimental study with a one-Group pretest-posttest design model where the researcher performs a pretest before the treatment is carried out and a posttest after the treatment is carried out. The sample of this study was the students of SMP Plus Al-Firdaus Malang class VII with a total of 28 students. The results of the study showed a significant increase after treatment was carried out in the form of the application of the CIRC method. This is evidenced by the average value of the pretest 63.1 increasing with the posttest average value of 86.1.